Theoretical analysis of charge flow rate at dye sensitized-semiconductor interfaces cell system - Mohsin A. Hassooni (Energy Reports, 2020)
The dynamics of charge flow at the interface of the Dye/Semiconductor cell has been investigated by a quantum transfer theory. At the interface between the N3 and Cresyl Violet CV dyes complex such as CdS and InAs semiconductor, the potential determines the flow charge transfer rate and indicates the efficiency of the devices. The flow charge rate at N3/CdS, N3/InAs, CV/CdS and CV/InAs were increased along with decreasing the energy of transition and increasing the coupling parameter. The potential at the interface also indicates the effect of the structure of the material on the flow charge rate in the dye-sensitized solar cells (DSSC) devices. The flow charge rate at DSSC system is polar dependent region. In this study, the flow charge rate was found to be highly compared to InAs by factor 10 2.
Keywords: 330; Flow charge; DSSC; Dye sensitized-semiconductor